The Effectiveness of Acupuncture Therapy in the Drug Addiction to Ward Off the Social Culture Threats - Dion Rukmindar; Elies Fitriani; Inria Chandra; Herlina Tarigan; Wahyuningsih Djaali (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
Drug addiction is a social-cultural threat and has a serious impact on national defense. It is required a comprehensive approach as it would influence the quality of the next generation. Treatment for drug addicts is called the rehabilitation process and one of the stages is the detoxification process, where drug-class substances are removed from the addict's body. The current detoxification process uses pharmacological and non-pharmacological methods. Acupuncture through the NADA (National Acupuncture Detoxification Association) protocol can be a non-pharmacological approach to the drug detoxification process by overcoming the weakness of previous pharmacological and non-pharmacological therapies. This article is a narrative review from the last ten years published in PubMed, Embase, Google Scholar, and Elsevier. This literature review aims to study whether or not acupuncture is a beneficial therapy in the detoxification process in the rehabilitation of drug addicts proven with scientifically based evidence. This result then could become a consideration for stakeholders to make a standard protocol in the rehabilitation process for drug users in Indonesia. Based on the studies reviewed in this literature review, the NADA protocol is feasible to become a non-pharmacological approach in the rehabilitation of drug addicts. Additional research on the use of the NADA protocol is needed.